Liquidity Ratios as Monetary Policy Tools : Some Historical Lessons for Macroprudential Policy - Monnet, Eric (IMF Working Papers; Working Paper ;, 2019)
This paper explores what history can tell us about the interactions between macroprudential and monetary policy. Based on numerous historical documents, we show that liquidity ratios similar to the Liquidity Coverage Ratio (LCR) were commonly used as monetary policy tools by central banks between the 1930s and 1980s. We build a model that rationalizes the mechanisms described by contemporary central bankers, in which an increase in the liquidity ratio has contractionary effects, because it reduces the quantity of assets banks can pledge as collateral. This effect, akin to quantity rationing, is more pronounced when excess reserves are scarce.